Lidocaine injections and neck corset wearing improve dropped head syndrome in Parkinson's disease and related disorders. (2019) - Mukai, Yohei; Furusawa, Yoshihiko; Morimoto, Yuko; Hama, Yuka; Kawazoe, Tomoya; Saitoh, Yuji; Sakamoto, Takashi; Takahashi, Yuji; Murata, Miho
Abstract: Background: Patients with Parkinson's disease and related disorders (PDRD) may exhibit dropped head syndrome (DHS), which does not yet have an effective treatment. Objectives: To evaluate the effect of combining lidocaine injection into the bilateral scalene muscles and neck corset wearing on dropped head syndrome. Methods: We performed needle electromyography assessments of the scalene, sternocleidomastoid (SCM), levator scapulae, splenius capitis, and trapezius muscles. Patients received 2.5–5 ml injections of 1% lidocaine into both sides of the scalene muscles for 4/5 consecutive days and were instructed to wear a neck corset. We measured the neck flexion angle, which formed between the horizontal line and the straight line passing through the ear canal and orbital fossa, before (baseline) and after (Day 8 and Day 90) the intervention. Results: Seven males and eight females (mean age, 68.9 years; range 56 to 85 years) who had PDRD with dropped head syndrome were enrolled in this study. Needle electromyography examination revealed abnormal discharge of the scalene muscles in all patients when the neck position was corrected; however, some patients did not show abnormal discharge of the SCM muscle. At Day 8, we observed an improvement of the neck flexion angle in 13 of the 15 patients, from an average of 27.7° ± 13.9° to 11.7 ± 14.6°. At Day 90, the average neck flexion angle was 15.3° ± 17.2°. Conclusions: Combining lidocaine injection into the scalene muscles and neck corset wearing is an effective treatment regimen for DHS in patients with PDRD.